Effect of Root Canal Preparation on Propagation of Dentinal Microcracks - do Nascimento, Bianca Mara Zakalusne; Chaves, Jardel Francisco Nazzi; Sousa-Neto, Manoel DamiÃ£o; Baratto-Filho, Flares; Tomazinho, FlÃ¡via Sens Fagundes; Leonardi, Denise Piotto (Iranian Endodontic Journal, 2021)
Introduction: This study evaluated the propagation of dentinal microcracks and the root canal volume increase after being prepared with two endodontic instruments: ProTaper Next (PTN) and WaveOne Gold (WOG) by micro-computed tomography analysis. Methods and Materials: We selected 48 maxillary molars randomly distributed in two groups: PTN and WOG. The samples were scanned before and after instrumentation, and then the image analysis was performed to detect the propagation of pre-existing dentinal micro-cracks and calculate the pre- and post-instrumentation volume. The statistical analysis was performed using Student’s t-test, Fisher’s exact test, and ANCOVA (P<0.05). Results: Dentinal microcracks were observed in 95.8% of the samples, both PTN and WOG instruments propagated microcracks after instrumentation, but there was no significant difference between the instruments (P=0.538). In relation to the root canal volume there was no statistic difference between PTN and WOG systems for the mesiobuccal (P=0.426) and distobuccal root canals (P=0.523). Conclusion: We can conclude that both ProTaper Next and WOG systems propagate dentinal microcracks after root canal preparation in this in vitro study, without statistical significance. The root canal volume prepared also showed no statistically significant difference between the two groups. This in vitro study requires further studies for more concrete conclusions.